2014
DOI: 10.1332/174426413x662770
|View full text |Cite
|
Sign up to set email alerts
|

Patient and public involvement in research in the English NHS: a documentary analysis of the complex interplay of evidence and policy

Abstract: The last 20 years have seen significant international shifts towards greater patient and public involvement (PPI) in health research and development (R&D). In England, then first health R&D strategy in 1991 did not mention PPI. Twenty years later, PPI is deeply embedded within the National Institute for Health Research. This article examines the evolving relationship between evidence and policy on PPI in research through a documentary analysis of English health R&D policy documents published betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Alongside this academic debate, a set of policy initiatives have encouraged greater PPI in health research . There has also been a significant investment in PES (particularly supported by science funders such as the UK Wellcome Trust) and activity by scientists to respond to public concerns about scientific issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside this academic debate, a set of policy initiatives have encouraged greater PPI in health research . There has also been a significant investment in PES (particularly supported by science funders such as the UK Wellcome Trust) and activity by scientists to respond to public concerns about scientific issues.…”
Section: Introductionmentioning
confidence: 99%
“…Alongside this academic debate, a set of policy initiatives have encouraged greater PPI in health research. 9 There has also been a significant investment in PES (particularly supported by science funders such as the UK Wellcome Trust) and activity by scientists to respond to public concerns about scientific issues. While PES is a more established concept for biomedical researchers, PPI has a growing currency particularly given its profile with funding bodies such as the UK National Institute for Health Research (NIHR).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, as a result of the programme of PPI, patient involvement has become an increasingly standard requirement for clinical and academic researchers (Evans 2014). At the same time, there is limited evidence demonstrating that PPI has changed clinical research practices (Boaz et al 2016, Rise et al 2013.…”
Section: Ethical Valuationmentioning
confidence: 99%
“…In a number of countries, the last 20 years have seen an explosion in public participation in health systems governance, health research governance and health promotion. In a recent paper, Evans tracked the evolution of public and patient involvement in research in the UK through an analysis of policy documents (2). Similar to Mockford et al (3), he found public and patient involvement to be deeply imbedded in research funding structures, but concluded that the drive to involve raced ahead of the establishment of an evidence base for participation.…”
mentioning
confidence: 93%